The Role of Higher Education Through the Eyes of Hungarian Undergraduate Students and Graduates: A Qualitative Exploratory Study - Zsófia Kocsis; Gabriella Pusztai (International Journal for Research in Vocational Education and Training)
Context: Most education systems equip graduates with the professional knowledge and cognitive skills needed to enter the world of work. However, there are other competencies also important for young graduates to become successful employees. Due to the growing uncertainty that characterizes the labour market, the demand for non-cognitive skills (communication, collaboration, critical thinking etc.) that support employee development potential and better integration has increased significantly. However, higher education institutions often transmit a culture that is different from that of workplaces. The aim of our study is to explore the role of the examined higher education institution in preparing students for the labour market. Our long-term goal is to support institutional development on the basis of this data.